Diabetic versus Non-Diabetic Patients with Complicated Urinary Tract Infections: A Prospective Comparative Study - Muhammad Ilyas, Muhammad Seerwan, Muhammad Adnan, Ibrar Ahmad, Saifullah, Ali Shandar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Complicated urinary tract infections (cUTIs) are associated with structural, functional, or systemic risk factors and are more severe than uncomplicated UTIs. Diabetes mellitus is a major predisposing factor, leading to impaired immunity, urinary stasis, and increased susceptibility to multidrug-resistant pathogens. This study aimed to compare clinical presentation, microbiological profile, treatment requirements, complications, and outcomes of cUTIs in diabetic versus non-diabetic patients. Methods: This prospective observational study was conducted at the Department of Urology, Gomal Medical College, DI Khan, from January 2023 to September 2023. A total of 134 adult patients with cUTIs were enrolled, comprising 67 diabetics (Group A) and 67 non-diabetics (Group B). Data on demographics, clinical features, laboratory investigations, urine culture results, antibiotic therapy, hospital stay, complications, and outcomes were collected. Statistical analysis was performed using SPSS, with p-values <0.05 considered significant. Results: Diabetic patients were older (54.2 ± 11.5 vs 47.5 ± 12.2 years) and more frequently presented with systemic symptoms such as fever (85.1% vs 73.1%) and flank pain (77.6% vs 61.2%). Escherichia coli was the predominant pathogen in both groups, while multidrug-resistant organisms were more common in diabetics (34.3% vs 14.9%). Diabetics required intravenous antibiotics more often (79.1% vs 56.7%) and had longer hospital stays (7.9 ± 3.1 vs 5.7 ± 2.4 days). Complications, including acute kidney injury and sepsis, were higher in diabetic patients. Complete recovery was achieved in 71.6% of diabetics versus 85.1% of non-diabetics. Conclusion: Diabetic patients with cUTIs exhibit more severe clinical presentations, higher prevalence of resistant pathogens, prolonged hospitalization, and slightly worse outcomes compared to non-diabetic patients. Early recognition, culture-guided therapy, and optimized glycemic control are essential to improve management and reduce complications in high-risk populations. Keywords: Complicated urinary tract infection, diabetes mellitus, multidrug-resistant organisms, hospitalization, outcomes.